2017
DOI: 10.1111/asj.12811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic supplementation and genotype on growth performance, carcass traits, hematological parameters and immunity of growing rabbits under hot environmental conditions

Abstract: The effect of dietary inclusion of probiotics and genetic groups on rabbit performance under hot environmental conditions was studied. A total of 80 rabbits aged 8 weeks were distributed into a completely randomized design in a 4 × 3 factorial arrangement, including four genetic groups and three concentrations of dietary probiotic (0, 200 and 400 g/t feed). The utilized probiotic contained 4 × 10 colony-forming units/g of Bacillus subtilis. Jabali local breed (J), imported Spanish V-line (V) and their crossbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
35
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 15 publications
11
35
3
4
Order By: Relevance
“…On the other hand, Cesari et al (2008), using a blend of formic and lactic acids in rabbit diets (30-84 days of age), found that dietary inclusion of organic acids had no effect on daily feed intake or growth rate of the fattening rabbits. Fathi et al (2017) found that dietary supplementation with probiotic (400 g/ton) achieved a significant increase in feed intake compared with control group. Ezema and Eze (2010) and Bhatt et al (2017) reported that probiotics had a positive effect on feed intake of growing rabbits.…”
Section: Feed Intakementioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, Cesari et al (2008), using a blend of formic and lactic acids in rabbit diets (30-84 days of age), found that dietary inclusion of organic acids had no effect on daily feed intake or growth rate of the fattening rabbits. Fathi et al (2017) found that dietary supplementation with probiotic (400 g/ton) achieved a significant increase in feed intake compared with control group. Ezema and Eze (2010) and Bhatt et al (2017) reported that probiotics had a positive effect on feed intake of growing rabbits.…”
Section: Feed Intakementioning
confidence: 92%
“…In agreement with the present results, Viliene et al (2017) found that dietary supplementation with organic acids, butyric acid, calcium formate or its salts did not significantly influence the carcass yield or the proportions of the various carcass parts. Fathi et al (2017) reported that dietary supplementation with probiotic led to significantly highter dressing percentage compared with those given the other dietary treatments. Chrastinová et al (2010) demonstrated that probiotics increased protein and fat contents in rabbit's carcass meat.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…The present results are consistent with the findings of Kermauner and Struklec (1996) observed that addition of probiotic Acid-Pack-4-way on the diet of rabbit increased (P≤0.05) the dressing percentage and carcass weight. Also, Fathi et al (2017) indicated that supplementation of dietary with probiotic compared to other dietary treatments resulted in a significantly higher percentage of dressing.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…Egypt's topographical location makes its weather mostly warm, with temperatures ranging from 23 to 32°C in summer versus 9 to 17°C in winter (El-Nahrawy, 2011). Thus, due to the climatic changes between summer and winter, various investigations have been conducted to study season influence on rabbit adaptation and their productivity (El-Sheikh et al, 2011;Fathi et al, 2017;Khalil, 2018). However, previous studies on the impact of climate on body cover properties in Egyptian rabbit breeds are lacking.…”
Section: Introductionmentioning
confidence: 99%